Factorial Analysis and Invariance Testing for Age and Gender of the Reactive-Proactive Aggression Questionnaire (RPQ) - Ronald Alberto Toro Tobar; Juan García-García; Flor Zaldívar- Basurto (International Journal of Psychological Research, 2020)
Reactive aggression is characterized by high emotional activation, impulsivity, and hostility, while proactive aggression presents a cold, instrumental, and planned strategy. The aim was to perform a psychometric analysis of the Reactive-Proactive Aggression Questionnaire [RPQ]. A non-probability sample of 502 people between 18 and 40 years old was formed, grouped by sex (n=297, 59.2% women and n=205, 40.8% men) and age (n = 224, 44.62% under 25 years old and n=278, 55.38% over 25 years old). The instruments were the RPQ, the Anger Rumination Scale (ARS), and an affective scale (PANAS) in printed format. In this instrumental psychometric study, we found that the RPQ fits better in a model of two factors interrelated with residual covariances (CFI = .928, RMSEA = .044), presenting significant correlations with negative affect and anger rumination, as evidence of validity of concurrent criterion, especially with reactive aggression (anger rumination r = .542, and negative affect r = .359). Also, the test was not invariant between sexes and ages, given that the best fit was in the male sex and those under 25 years of age (∆CFI < 0.01, ∆RMSEA < 0.015). We concluded that women and adults over the age of 25 have a different aggressive response profile. These findings represent new directions of research around the measurement of aggressive behavior and the development of gender differentiated interventions for adolescents and young adults.